Juridical Review Process of Land Selling That Was Conducted in Bad Intention: (Study of Supreme Court Decision Number 1545K/Pdt/2019) - Rahmat Lubis; Bastari; Utary Maharany Barus; Maria (LEGAL BRIEF, 2022)
The existence of the earth cannot be separated from human life, the state is obliged to guarantee and protect the rights of citizens to acquire, own and enjoy property rights over land. However, because land area is determined by the increasing needs of the state's economy, this often creates land disputes as stated in the Supreme Court Decision 1545/K/Pdt/2019, where one party obtains ownership rights to land in good faith. This research is descriptive in nature and uses a normative legal approach. Information obtained through library research (library research). Based on the research results, there are vague indications that fraudulent acts may contain an element of offense under § 531 BGB, namely. H. the buyer knows the defect of the goods, but the buyer still buys the goods and the legal consequences of transferring the property can be canceled and the rights can be returned to the original owner, the buyer can also be punished for all costs, losses and interest incurred. From this it can be concluded that the form of fraud in Decision No. 1545/K/Pdt/2019 because the purchase of goods by Defendant II to Pelawan is invalid because it is no longer the direct owner, so it is appropriate that Pelawan's resistance cannot be accepted because it is against the law.